2017
DOI: 10.1371/journal.pone.0177074
|View full text |Cite
|
Sign up to set email alerts
|

The association of dietary vitamin C intake with periodontitis among Korean adults: Results from KNHANES Ⅳ

Abstract: BackgroundsThe association of dietary vitamin C (vit C) on periodontitis requires more valid evidence from large representative samples to enable sufficient adjustments. This study aimed to evaluate the association between dietary vit C intake and periodontitis after controlling for various confounders in the representative Korean adult populationMethodA total of 10,930 Korean adults (≥19 years) from the fourth Korean National Health and Nutrition Examination Survey data set were included in this cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 40 publications
0
33
0
3
Order By: Relevance
“…Selected potential confounders were socio‐demographic factors (age, sex, monthly household income) and general health‐related behaviours (physical activity, alcohol drinking, lifetime cigarette smoking amount) (Han, Lim, Sun, Paek, & Kim, ; Lee, Shin, Kim, Ahn, & Kim, ) and systemic health factors (diabetes, hypercholesterolaemia, hypertension, obesity). Socio‐demographic factors and general health‐related behaviours were collected using standardized self‐administered questionnaires through face‐to‐face interview, while the systemic health factors were evaluated using blood analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Selected potential confounders were socio‐demographic factors (age, sex, monthly household income) and general health‐related behaviours (physical activity, alcohol drinking, lifetime cigarette smoking amount) (Han, Lim, Sun, Paek, & Kim, ; Lee, Shin, Kim, Ahn, & Kim, ) and systemic health factors (diabetes, hypercholesterolaemia, hypertension, obesity). Socio‐demographic factors and general health‐related behaviours were collected using standardized self‐administered questionnaires through face‐to‐face interview, while the systemic health factors were evaluated using blood analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In a study with 10,930 patients, Lee et al [59] found that in patients with DM between the ages of 30 and 49, there was a significant link between vitamin C intake and periodontitis. In the stratified analysis, the aforementioned association was highlighted among patients with type 2 DM.…”
Section: Vitamin C Dm and Pdmentioning
confidence: 99%
“…From these 46 potential relevant articles, 31 did not meet the criteria. Finally, 15 publications (7 cross-sectional studies [23][24][25][26][27][28][29], 2 case-control studies [30,31], 2 cohort studies [32,33]), and 4 RCTs [34][35][36][37]) were selected for systematic review, as shown in the flow chart ( Figure 1). Excluding the RCTs, 6 of the remaining 11 studies estimated vitamin C intake from dietary investigation and 6 studies measured blood vitamin C concentration.…”
Section: Literature Searches and Study Characteristicsmentioning
confidence: 99%
“…With regard to exposure, 4 cross-sectional studies [23][24][25][26], one case-control study [31] and one cohort study [32] assessed dietary intake. Of these studies, five used dietary recall [23][24][25][26]31], specifically, two studies used multiple dietary recalls [24,31], and three used a single dietary recall [23,25,26]. Since a single 24-h dietary recall could not be considered to reflect one's habitual diet [38], multiple 24-h recalls are desirable and this technique was rated as "satisfactory".…”
Section: Quality Evaluationmentioning
confidence: 99%
See 1 more Smart Citation